Risk of Hospital Encounters With Kidney Stones in Autosomal Dominant Polycystic Kidney Disease: A Cohort Study. (March 2021) - Kalatharan, Vinusha; Welk, Blayne; Nash, Danielle M.; Dixon, Stephanie N.; Slater, Justin; Pei, York; Sarma, Sisira; Garg, Amit X.
Background: There is a perception that patients with autosomal dominant polycystic kidney disease (ADPKD) are more likely to develop kidney stones than the general population. Objective: To compare the rate of hospital encounter with kidney stones and the rate of stone interventions between patients with and without ADPKD. Design: Retrospective cohort study. Setting: Ontario, Canada. Patients: Patients with and without ADPKD who had a prior hospital encounter between 2002 and 2016. Measurements: Rate of hospital encounter with kidney stones and rate of stone intervention. Methods: We used inverse probability exposure weighting based on propensity scores to balance baseline indicators of health between patients with and without ADPKD. We followed each patient until death, emigration, outcomes, or March 31, 2017. We used a Cox proportional hazards model to compare event rates between the two groups. Results: Patients with ADPKD were at higher risk of hospital encounter with stones compared with patients without ADPKD (81 patients of 2094 with ADPKD [3.8%] vs 60 patients of 1902 without ADPKD [3.2%]; 8.9 vs 5.1 events per 1000 person-years; hazard ratio 1.6 [95% CI, 1.3-2.1]). ADPKD was not associated with a higher risk of stone intervention (49 of 2094 [2.3%] vs 47 of 1902 [2.4%]; 5.3 vs 3.9 events per 1000 person-years; hazard ratio 1.2 [95% CI = 0.9-1.3]). Limitations: We did not have information on kidney stone events outside of the hospital. There is a possibility of residual confounding. Conclusion: ADPKD was a significant risk factor for hospital encounters with kidney stones.